The Theory of ’’Global Islamic State’’: A special study of Medinan Life of Prophet Muhammad PBUH (A response to Hallaq’s impossible state) - Dr.Abdul Basit; Dr. Mahmood Ahmad (Seerat Studies, 2023)
Considering the implementation of Islamic Sharia, Wael B. Hallaq claims that the concepts of the modern state and the Islamic state are incompatible. The primary cause of this is the inconsistency between their respective central domains. Colonialism is the primary reason behind the issues facing the Islamic states. Regarding these issues, it may be concurred with Hallaq. In a same vein, Hallaq's call for change and critique of the contemporary states may be endorsed. However, there are issues with these research's conclusions, ramifications, and suggested solutions. It is a fact that the emergence of a global Islamic state is becoming inevitable and that the rule of law is the only viable form. It is expected that analysts such as Hallaq won't be hesitated to acknowledge this possibility of Global Islamic State. There are two possible situations for being established a global Islamic state. The western scholars, in one perspective, will not hesitate to accept it, nevertheless, in another perspective, they too face a significant obstacle. Considering above facts, we have explored the potential for being establish a worldwide Islamic state in this paper.